On the Roman Villas on the south of province of Dalmatia (Several examples from the area of East Herzegovina) - Samardžić, Gligor M. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
This paper presents the data regarding Roman villas in the valley of the Trebišnjica River in East Herzegovina (south of province of Dalmatia). The bases for successful research of Roman villas in this region are original written records and material remnants on the terrain (epigraphic monuments, remnants of buildings, settlements, and roads, fragments of bricks, roof tiles, processed stone, Roman ceramics, glass, vessels and amphorae, fragments of frescoes, mosaics, torcularium, money etc.). Archeological discoveries point out that continuity of populating this region could be traced from prehistorical period until modern age. The area which will be researched in this paper is located near the Trebišnjica River. It is the area with very convenient climate conditions for the development of agriculture and livestock farming. It caused this region to be populous in ancient time. In this paper we will present discoveries from Roman time from the locations of Crkvina–Prežani (villа urbanа), Dračeva strana (villa rustica), Potkućnice (villa rustica) and villa rustica very close to bank of the Trebišnjica River (Panik) southern from Bileća, Mirina and Lijeska villa rustica (Bihovo) near Trebinje, as well as the location of Tanoge in Ljubomir (villa rustica) northern from Trebinje.